Saudi Arabia strives to become major player in mineral supply chains: A questionable pillar of Europe's diversification strategy - Meike Schulze; Mark Schrolle (Stiftung Wissenschaft und Politik (SWP), 2024)
Saudi Arabia has entered the geopolitical competition for mineral resources - and it has done so in a determined manner and with substantial funds at its disposal. As part of its Vision 2030, the Kingdom aims to strengthen local processing and industrial value added. Currently, Saudi Arabia secures its mineral resources through international investments and offtake agreements; but, in the long term, it plans to develop its domestic mining industry. Many initiatives remain in the conceptual phase. As it looks to realise its ambitions, Saudi Arabia continues to rely on international partners. Positioning itself as a geopolitically neutral "link" between the major powers, the Kingdom is seeking closer ties with China while at the same time competing with the People's Republic. Simultaneously, it presents itself to the West as a potential partner for resource diversification. The EU appears to regard cooperation with Saudi Arabia as a viable option for securing its raw material supply. However, the key conditions for a strategic partnership have still not been met.
Keywords: 320; Saudi Arabia; Mineral Supply Chains; Saudi Arabian Mining Company (Ma'aden); "Vision 2030"; European Union (EU); mining industry; China; resource diversification; Critical Raw Materials Act (CRMA); Saudi Public Investment Fund (PIF); gold; phosphate; bauxite; copper; zinc; feldspar; silver; Gulf Cooperation Council (GCC); EU Corporate Sustainability Due Diligence Directive (CSDDD); Carbon Border Adjustment Mechanism (CBAM); International Governmental Forum on Mining and Minerals (IGF)